2006
DOI: 10.1007/s00415-006-7009-0
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss in Parkinson’s disease

Abstract: Weight loss is frequent in patients with Parkinson's disease (PD). Reduced energy intake and/or increased energy expenditure have been postulated as the cause. Dysphagia, anorexia, and gastrointestinal dysfunction may be possible causes of reduced energy intake; whereas, rigidity, tremor, and levodopa-induced dyskinesia may increase energy expenditure. Levodopa may enhance glucose metabolism resulting in enhanced energy expenditure. Depression, anti-parkinsonian drugs, and medical complications such as pneumon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 26 publications
1
83
0
2
Order By: Relevance
“…It has been shown that PD patients lose weight despite having adequate or even increased energy intakes (Kashihara, 2006). For what concerns eating habits, a preference for sweet food such as, for instance, cakes (Lorefält, Granérus, & Unosson, 2006), chocolate (Wolz et al, 2009), ice cream (Meyers, Amick, & Friedman, 2010), and carbohydrates (Adén et al, 2011;Hellenbrand et al, 1996;Lorefält et al, 2006), has been documented.…”
Section: Dietary Habits and Food Intakementioning
confidence: 98%
See 2 more Smart Citations
“…It has been shown that PD patients lose weight despite having adequate or even increased energy intakes (Kashihara, 2006). For what concerns eating habits, a preference for sweet food such as, for instance, cakes (Lorefält, Granérus, & Unosson, 2006), chocolate (Wolz et al, 2009), ice cream (Meyers, Amick, & Friedman, 2010), and carbohydrates (Adén et al, 2011;Hellenbrand et al, 1996;Lorefält et al, 2006), has been documented.…”
Section: Dietary Habits and Food Intakementioning
confidence: 98%
“…The purposes of the present review are, first, to summarize the studies that assessed the weight and eating habits in PD patients and, second, to examine the possible contribution of some non-motor symptoms to weight and food intake alterations. In particular, the review will consider nonmotor symptoms affecting sensory perception, cognition, mood and By and large, PD patients have been observed to lose weight and to be more frequently underweight (Body Mass Index, BMI < 20 kg/ m 2 ; Bachmann & Trenkwalder, 2006;Kashihara, 2006;Kistner et al, 2014, for recent reviews), with a high risk of malnutrition (Fereshtehnejad et al, 2014;Sheard, Ash, Mellick, Silburn, & Kerr, 2013a;Sheard, Ash, Silburn, & Kerr, 2013b). The weight loss has been described even before diagnosis (Chen et al, 2003).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Possible determinants of weight loss in PD patients include hyposmia, impaired hand-mouth coordination, difficulty chewing, dysphagia, intestinal hypomotility, depression, decreased reward processing of DAergic mesolimbic regions, nausea, and anorexia as the side effects of medication, and increased energy requirements due to muscular rigidity and involuntary movements. There is enough evidence for recommending monitoring the body weight of PD patients as the disease progresses [147].…”
Section: Obesitymentioning
confidence: 99%
“…Others. Weight loss [Kashihara, 2006] and fatigue [Friedman et al 2007] may be associated with PD and ZNS may potentiate them, therefore they should be taken into account when treating PD with ZNS.…”
Section: Neuroprotectionmentioning
confidence: 99%